Development of an ID ICP-MS reference method for the determination of Cd, Hg and Pb in a cosmetic powder certified reference material. Issue 4 (8th January 2016) - Kim, Sook Heun; Lim, Youngran; Hwang, Euijin; Yim, Yong-Hyeon
Abstract : Accurate measurement of hazardous elements in cosmetics is considerably important in response to cosmetic safety issues. Abstract : Accurate measurement of hazardous elements in cosmetics is considerably important in response to cosmetic safety issues. A sample preparation method using microwave-assisted acid digestion combined with double isotope dilution inductively coupled plasma/mass spectrometry (ID ICP-MS) was used for the certification of the hazardous elements, Cd, Hg and Pb, in cosmetic powder samples. The HF-free sample preparation method was validated and applied to analyse Cd and Pb in cosmetic powder. The Hg content in the sample was determined by employing a fast valve sample introduction system to resolve the severe memory effect in Hg analysis. Homogeneity and stability were also evaluated. The certified values of Cd, Hg and Pb were (24.8 ± 1.3) mg kg −1, (0.648 ± 0.065) mg kg −1 and (24.55 ± 0.31) mg kg −1, respectively. The relative combined standard uncertainty was 2.7% for Cd, 5.1% for Hg and 0.62% for Pb. The detailed procedure for certification and evaluation of the associated uncertainty is also presented. The proper use of the developed CRM for quality control and method validation in testing laboratories and the cosmetic industry is expected to significantly improve the reliability and quality of test results for hazardous elements in cosmetics, thereby contributing to cosmetic safety.